William Meed in the Yukon Dock Company office, Dawson, Yukon Territory, 1900. - Severance, Charles
PH Coll 246.227 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number